Development of Mucoadhesive Chitosan Derivatives for Use as Submucosal Injections - Hidemi Hattori (Polymers, 2018)
Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) have been used for surgical treatment of early gastric cancer. These endoscopic techniques require proper submucosal injections beneath the tumor to provide a sufficiently high submucosal fluid cushion (SFC) to facilitate clean dissection and resection of the tumor. Until now, the submucosal injection materials developed for endoscopic techniques such as EMR and ESD of tumors have been composed of macromolecules, proteins, or polysaccharides. We have been investigating the use of chitosan, a product that is obtained by the alkaline deacetylation of chitin, the second-most abundant natural polysaccharide. Specifically, we have been studying a photocrosslinked chitosan hydrogel (PCH) and solubilized chitosan derivatives for use as novel submucosal injections for endoscopic techniques. Notably, chitosan derivatives with lactose moieties linked to the amino groups of its glucosamine units can specifically interact with acidic mucopolysaccharides and mucins in submucosa without the need for the incorporation of harmful photoreactive groups nor potentially mutagenic ultraviolet irradiation.